1995
DOI: 10.1139/f95-092
|View full text |Cite
|
Sign up to set email alerts
|

Planktivory by alewife (Alosa pseudoharengus) and rainbow smelt (Osmerus mordax) on microcrustacean zooplankton and dreissenid (Bivalvia: Dreissenidae) veligers in southern Lake Ontario

Abstract: The objective of this study was to describe the diet of young-of-the-year and adult alewife (Alosa pseudoharengus) and rainbow smelt (Osmerus mordax) in nearshore waters coincident with the colonization of Lake Ontario by Dreissena. Laboratory experiments and field observations indicated that alewife and rainbow smelt consumed dreissenid veligers and that the veligers remained intact and identifiable in the digestive tract for several hours. Dreissenid larvae were found in field-caught alewife and rainbow smel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…Although D. polymorpha has been intensively investigated for over a century (Schloesser et al, 1994), only 10 European and 5 North American fish species were found to feed on its planktonic larvae, and reported FO and biomass values of D. polymorpha larvae in the diets of these species are usually lower than those found in our study (e.g., Mills et al, 1995;Molloy et al, 1997). The moderate trophic impact of D. polymorpha veligers on other members of the ecosystem was recently confirmed by stable isotopic studies in estuarine waters (Barnard et al, 2006).…”
Section: Discussioncontrasting
confidence: 73%
“…Although D. polymorpha has been intensively investigated for over a century (Schloesser et al, 1994), only 10 European and 5 North American fish species were found to feed on its planktonic larvae, and reported FO and biomass values of D. polymorpha larvae in the diets of these species are usually lower than those found in our study (e.g., Mills et al, 1995;Molloy et al, 1997). The moderate trophic impact of D. polymorpha veligers on other members of the ecosystem was recently confirmed by stable isotopic studies in estuarine waters (Barnard et al, 2006).…”
Section: Discussioncontrasting
confidence: 73%
“…Comparisons with D. polymorpha suggest that its much shorter reproductive period (Nichols 1996) may be among the reasons for its considerably lower presence in the diet of North American fish species. According to Mills et al (1995), only two North American fish species feed on D. polymorpha larvae (as opposed to at least 11 species recorded to feed on L. fortune larvae in South America; Paolucci et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Note that the decrease in Wsh catch was related to a drop in commercial Wshing following the reuniWcation of Germany in 1989/1990; however, stocking of Wsh was also reduced at the same time, pointing to a probable stable Wsh abundance on a lower level at the beginning of the 1990s. Mills et al (1995) showed that, in years when planktivorous Wsh were abundant and larvae sparse, planktivorous Wsh could substantially reduce larval numbers in a fairly short period. Therefore, it is likely that improved food composition and/or a probable decrease in Wsh abundance have enhanced conditions for survival of large larvae within the years of cluster D.…”
Section: Discussionmentioning
confidence: 99%